2019
DOI: 10.1002/mp.13737
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of penh, fluka, and Geant4/topas for absorbed dose calculations in air cavities representing ionization chambers in high‐energy photon and proton beams

Abstract: Purpose The purpose of this work is to analyze whether the Monte Carlo codes penh, fluka, and geant4/topas are suitable to calculate absorbed doses and fQ/fQ0 ratios in therapeutic high‐energy photon and proton beams. Methods We used penh, fluka, geant4/topas, and egsnrc to calculate the absorbed dose to water in a reference water cavity and the absorbed dose to air in two air cavities representative of a plane‐parallel and a cylindrical ionization chamber in a 1.25 MeV photon beam and a 150 MeV proton beam — … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…Therefore, the Type B uncertainty associated with the fQ/fQ0 ratios presented here may differ from the estimation in Wulff et al 9 and Baumann et al 8 due to differences in the cross‐section data and particle transport of the codes. Baumann et al 40 investigated the impact of combining a fQ factor determined in TOPAS/Geant4 and a fQ0 calculated in EGSnrc and found that the resulting difference from using the same code for both factors is (0.3 ± 0.2)%.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the Type B uncertainty associated with the fQ/fQ0 ratios presented here may differ from the estimation in Wulff et al 9 and Baumann et al 8 due to differences in the cross‐section data and particle transport of the codes. Baumann et al 40 investigated the impact of combining a fQ factor determined in TOPAS/Geant4 and a fQ0 calculated in EGSnrc and found that the resulting difference from using the same code for both factors is (0.3 ± 0.2)%.…”
Section: Discussionmentioning
confidence: 99%
“…The type B uncertainty of Monte Carlo calculated (D w /D air )60 Co ratios (due to uncertainties in the radiation physics and transport models, geometry, etc.) were estimated to be 0.5% based on an intercode comparison by Baumann et al [33] and a benchmark experiment by Renner et al [40]. The corresponding type B uncertainty of the (D w /D air ) heavy ion ratios from FLUKA simulations is more difficult to estimate but certainly larger than the uncertainty for 60 Co photons.…”
Section: Uncertainty Analysismentioning
confidence: 99%
“…Today advanced computational methods, in particular powerful Monte Carlo codes, are available to study the response of ionization chambers in different radiation fields [29][30][31][32]. The calculation of k Q factors by means of Monte Carlo simulation can be also described by Equation (7) [33,34]:…”
Section: Beam Quality Correction Factor K Qmentioning
confidence: 99%
See 2 more Smart Citations